2022
DOI: 10.7759/cureus.28547
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Intralesional Tranexamic Acid Versus Topical 4% Hydroquinone in Treating Melasma

Abstract: Objectives: To compare the efficacy of intralesional tranexamic acid and topical 4% hydroquinone in the treatment of melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Similar hepatoprotective effect against AFs-induced liver damages in poults is also found in another study (101). In the same studies a better gain in body weight was found in poults fed on diet supplemented with S. marianum or Silymarin and additionally treated with AFs (101,102). In the same experiments, it was found that the feed conversion ratio and the gain in body weight were increased when such chicks were supplemented by S. marianum and the measured indices were not different when compared to poults supplemented only by AFs-binder (102).…”
Section: Plant/herbal or Vitamin Additivesupporting
confidence: 74%
See 4 more Smart Citations
“…Similar hepatoprotective effect against AFs-induced liver damages in poults is also found in another study (101). In the same studies a better gain in body weight was found in poults fed on diet supplemented with S. marianum or Silymarin and additionally treated with AFs (101,102). In the same experiments, it was found that the feed conversion ratio and the gain in body weight were increased when such chicks were supplemented by S. marianum and the measured indices were not different when compared to poults supplemented only by AFs-binder (102).…”
Section: Plant/herbal or Vitamin Additivesupporting
confidence: 74%
“…In the same studies a better gain in body weight was found in poults fed on diet supplemented with S. marianum or Silymarin and additionally treated with AFs (101,102). In the same experiments, it was found that the feed conversion ratio and the gain in body weight were increased when such chicks were supplemented by S. marianum and the measured indices were not different when compared to poults supplemented only by AFs-binder (102). Such an increase in the gain of body weight was also seen in rats supplemented with W. somnifera (118).…”
Section: Plant/herbal or Vitamin Additivementioning
confidence: 61%
See 3 more Smart Citations